The Analysis of “Good Rural Season” Under the Background of the Revitalization of Rural Culture - Yong Liu; Lin Liu; Tao Wang; Yanxia Liu (Journal of World Economy, 2023)
“Good rural season” is a brand of “Season · Solar Term” rural tourism, which is based on popular culture and local culture. The theme of “good rural season” with the regional characteristics of Shandong province is full of wonderful activities, which promote the cultural and ecological revitalization of the countryside, enabling the revitalization of the countryside. The theme of “good rural season” is an integral part of the popular culture, which fully embodies the physical conditions of the historical geography, folk customs and aesthetic standards of Shandong province. It embodies the rich and colorful beauty of life and the best way of life and the good wishes of welcoming Xiang naifu and the basic moral norms of “dedication and friendliness”. This accords with people’s positive psychological demands and refracts the positive value orientation.